Primary and secondary signals of variations in the Denmark Strait Overflow over the last glacial cycle - Millo, Christian (2005)
In this study we present a reconstruction of the Denmark Strait Overflow over the last glacial cycle on the basis of five new and several published planktic and epibenthic stable isotope records obtained from sites to the north and south of the Denmark Strait.